Belgium : Selected Background Issues. (IMF Staff Country Reports; Country Report, 1996)
This Selected Background Issues paper analyzes sectoral wage differentiation and labor cost issues in Belgium. The paper discusses wage dispersion across sectors in Belgium and compares it with the pattern in other European countries. It analyzes the data for the Organization for Economic Cooperation and Development used in the Central Economic Council assessment of competitiveness, underscoring the role of social security contributions and restrictions on part-time work in the evolution of labor costs per employee. The paper also examines trends in saving and investment, and the pension reform in Belgium.